Evaluation of the estrogenic effects of UV filters on the sergeant major damselfish, Abudefduf saxatilis - Mélina Soto; Gabriela Rodríguez-Fuentes (Ciencias Marinas, 2014)
Oxybenzone, octyl salicylate, and octinoxate are compounds used in a variety of products as a protection against exposure to ultraviolet radiation. Concerns have emerged regarding their environmental safety as previous studies have shown that they tend to bioaccumulate and act as potential xenoestrogens in aquatic organisms. To our knowledge no studies have investigated their impact on tropical reef-associated species. Thus, the aim of the present study was to evaluate the estrogenic effects of these three compounds on the abundant, reef-associated sergeant major damselfish, Abudefduf saxatilis. As no genomic information of A. saxatilis was available, the first part of the study was to isolate and to sequence the vitellogenin (VTG) and β-actin genes. In the second part, the potential estrogenicity of the three compounds in juvenile fish (<5 cm) was studied using gene expression and protein synthesis analyses to evaluate the induction of VTG. Fish were exposed to doses of 5, 25, and 50 µg–1 of oxybenzone, octyl salicylate, octinoxate, and to a mixture of them in a similar proportion to the one used in commercial personal care products. An increment in alkali-labile phosphate was observed in all treatments, but it was only statistically significant in the positive control (17 β-estradiol). Relative gene expression was only statistically augmented in the positive control.